Exploring sources of competitive advantage among logistics service providers in the Americas. Issue 1 (2nd January 2017) - Lambourdière, Eric; Rebolledo, Claudia; Corbin, Elsa
ABSTRACT: This article describes differences among logistics service providers (LSPs) in their resource management decisions as they seek competitive advantage in an uncertain business environment. Using the resource-based theory and dynamic capabilities as theoretical backdrop, the authors find that four case LSPs in the Americas structure and bundle their resource portfolios to build capabilities, which they leverage to create and maintain value. Leveraging strategies and performance levels, which are influenced by environmental context, differ among the firms. This research enhances understanding of the constructive impact of resources and capabilities on LSP performance.